2021
DOI: 10.1055/a-1408-4793
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiological Response to Light- and Heavy-load Power-oriented Exercise in Older Adults

Abstract: This study investigated the acute responses to volume-load-matched heavy-load (80% 1RM) versus light-load (40% 1RM) power-oriented resistance training sessions in well-functioning older adults. Using a randomized cross-over design, 15 volunteers completed each condition on a leg press. Neuromuscular (maximal isometric force and rate of force development) and functional performance (power during sit-to-stand test), lactate, and muscle damage biochemistry (creatine kinase, lactate dehydrogenase and C-reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…44 Additionally, other recent studies investigating adaptations to low-load power training in older participants have also been published. 45,46 The results from the GPT group are consistent with previous studies showing that a combination of heavy and low loads induces superior increases in power across the entire FV curve compared to training with either heavy or low loads alone. 39,40 Thus, it is speculated that power training with a combination of load ranges can affect both force-and velocity-related adaptations, resulting in greater total adaptation in power compared to training programs aiming at specifically force-or velocity-related adaptations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…44 Additionally, other recent studies investigating adaptations to low-load power training in older participants have also been published. 45,46 The results from the GPT group are consistent with previous studies showing that a combination of heavy and low loads induces superior increases in power across the entire FV curve compared to training with either heavy or low loads alone. 39,40 Thus, it is speculated that power training with a combination of load ranges can affect both force-and velocity-related adaptations, resulting in greater total adaptation in power compared to training programs aiming at specifically force-or velocity-related adaptations.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, a recent study in older subjects has, however, observed load‐specific adaptations in V 0 following low‐load power training 44 . Additionally, other recent studies investigating adaptations to low‐load power training in older participants have also been published 45,46 . The results from the GPT group are consistent with previous studies showing that a combination of heavy and low loads induces superior increases in power across the entire FV curve compared to training with either heavy or low loads alone 39,40 .…”
Section: Discussionsupporting
confidence: 83%
“…In this sense, a recent study (2) suggested that impaired muscle power might have its origin in deficits in both force and velocity, being both deficits associated with a lower physical function, quality of life, and higher frailty, whereas only force deficit was associated with a lower cognitive function. A more recent study by the same group (38) found that heavy-load power training improved the capability to generate large forces, whereas low-load power training enhanced movement velocity in older adults. Nevertheless, both interventions promoted similar increases in muscle power and muscle hypertrophy (38).…”
Section: Discussionmentioning
confidence: 98%
“…The study of the cardiovascular and neuromuscular adaptations produced by power training programs conducted under different loading conditions has received increasing attention (5,14,16). However, these and other studies used markedly different loads related to not equated levels of power (11,14,38,40); thus, the effects of load and velocity on the strength performance and functionality of older adults remain unclear. To the best of our knowledge, this is the first study on older people comparing the effects of 2 PRT equated by the power level close to the PP but differing in load and, consequently, in velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation